Role of receptor protein and membrane lipids in xanomeline wash-resistant binding to muscarinic M1 receptors - Jakubík, Jan; Tucek, Stanislav; El-Fakahany, Esam E (The Journal of pharmacology and experimental therapeutics, 2004)
Xanomeline is a novel agonist functionally selective for muscarinic receptors of the M1 subtype. It binds to this receptor in two modes, reversible and quasi-irreversible (wash-resistant). We investigated the unknown mechanism of the wash-resistant binding in experiments with muscarinic M1 receptors expressed in transfected Chinese hamster ovary cells. Xanomeline's structure consists of two heterocycles and O-hexyl side chain. We compared the wash-resistant binding of xanomeline and its analogs with shorter O-alkyl side chains. For the wash-resistant binding to occur, the O-alkyl chain had to be at least O-butyl or longer. Accumulation of inositol phosphates was enhanced in washed cells that had been preexposed to xanomeline or its pentyl analog, whereas the agonistic effects of the methyl, propyl, and butyl analogs were abolished by washing. Only the reversible binding of xanomeline was detected purified soluble receptors, but both binding modes occurred purified receptors reconstituted into liposomes and exposed xanomeline only after reconstitution. The wash-resistant binding did not occur if the exposure of purified receptors or liposomes alone to xanomeline, followed by washing, reconstitution. Simultaneous presence of receptors and lipid environment is therefore essential for the binding to take place. We suggest that the binding of xanomeline involves interhelical penetration of M1 muscarinic receptor by xanomeline's O-alkyl chain and interaction with membrane lipids surrounding the receptor.
Keywords: CHO buňky; Inositol Phosphates; křečci praví; thiadiazoly; Temperature; Thiadiazoles; teplota; Female; Liposomes; zvířata; CHO Cells; Pyridines; ženské pohlaví; kompetitivní vazba; liposomy; Binding, Competitive; pyridiny; inositolfosfáty; Cricetinae; Receptor, Muscarinic M1; Animals; receptor muskarinový M1; Muscarinic Agonists; agonisté muskarinových receptorů